The Influence of Workload, Organizational Changes and Work Environment on Employee Performance at Agency of Planning and Development Area of Research And Development - Adris, Mohammad; Darmanto, Darmanto; Aripin, Sofjan (Universitas Negeri Makassar, 2023)
This study aims to determine the effect of workload, organizational change and work environment on the performance of employees of the Regional Planning and Development Agency for Research and Development in Paser Regency. The type of research used in this research is quantitative research with an associative approach. The population in this study were all employees of the Paser District Research and Development Agency, consisting of 81 employees. The samples taken in this study were all civil servants who worked in the office of all Bappedalitbang Paser Regency employees as many as 51 people. Data analysis in this study used multiple linear regression analysis with the SPSS 21 calculator. The results of the data analysis showed that there was an effect of workload on employee performance by looking at a significance value of 0.036 meaning < than 0.05, there was an influence of organizational change on employee performance by looking at a significance value of 0.014 meaning < than 0.05, there is no influence of the work environment on employee performance seeing a significance value of 0.097 meaning > than 0.05. Furthermore, the simultaneous test results show that there is a significant value of the simultaneous regression model of 0.000, this value is smaller than the significance level of 0.05 (5%), which is 0.000, which means workload, organizational change and work environment jointly affect performance.